Peran Mandolin sebagai Instrumen Melodis dalam Musik Dangdut: Studi Kasus pada Sarana Hiburan di Kota Pontianak - Nisa, Hayatun; Zakarias Aria Widyatama Putra (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
The mandolin, a type of chordophone instrument originating from Italy and was introduced to Indonesia in the 19th century. Recognized for its melodic character, the mandolin warrants in-depth exploration, particularly regarding its function as a secular musical instrument. Its presence significantly influences public appreciation in Pontianak, especially when featured in dangdut performances as a form of entertainment. This study aims to examine the role of the mandolin as a melodic instrument in dangdut music used for entertainment purposes in Pontianak City. A qualitative research approach was adopted, utilizing a case study method. The case was explored descriptively through data obtained from observations, in-depth interviews, and documentation. Data validity was ensured through methodological triangulation and extended observation. Data analysis involved reduction, presentation using mind maps, and drawing conclusions. The findings reveal that the mandolin plays a vital role as both a musical identity and a reinforcing element in dangdut music. In its role as an entertainment medium, the mandolin contributes to the enthusiasm and appreciation of the Pontianak community for dangdut music. This research is significant as it highlights the mandolin’s legitimizing role and distinctive contribution to dangdut, offering an alternative model for incorporating melodic instrument variations into similar musical performances.